DECISION SUPPORT SYSTEM FOR ADMISSION OF PROSPECTIVE STUDENT ASSOCIATION MEMBERS WITH THE PROMETHEE METHOD - Lowell, Andrew; Atmojo, Wahyu Tisno (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: This study examines how promethee can be a suitable method to be used in the decision-making system of prospective student association members as an organization under the auspices of the university. In this study, it is explained that the decision-making system for the acceptance of prospective student associations as an organization within the university environment experiences several problems in the process, namely, most of the associations still use the manual method. This of course not only has an impact on the effectiveness of the time and energy used but also affects the decisions taken. Promethee is one of the methods in the decision-making system that can be used by students considering that promethee is more efficient in time, effort, and objectivity in making better decisions. Researchers in this study also analyze and describe the scheme or flow of the promethee method that can be used by students as well as basic criteria such as academic, activeness, nature, and confidence possessed. This basic criterion can be one of the reference guidelines used in the selection and decision-making stages.            Keywords: decision making system; promethee; student association  Abstrak: Penelitian ini mengkaji tentang bagaimana promethee bisa menjadi salah satu metode yang cocok untuk digunakan dalam sistem pengambilan keputusan calon anggota himpunan mahasiswa sebagai organisasi yang berada di  naungan universitas. Penelitian ini menjelaskan bahwasanya sistem pengambilan keputusan penerimaan calon himpunan mahasiswa sebagai organisasi yang berada di lingkungan universitas mengalami beberapa masalah dalam prosesnya yakni Sebagian besar himpunan masih menggunakan metode yang manual. Hal ini tentu tidak hanya berdampak pada efektivitas waktu dan tenaga yang digunakan melainkan juga mempengaruhi keputusan yang diambil. Promethee menjadi salah satu metode dalam sistem pengambilan keputusan yang bisa digunakan oleh mahasiswa mengingat promethee lebih efisien dalam waktu, tenaga hingga tingkat objektivitas dalam pengambilan keputusan yang lebih baik. Peneliti dalam kajian ini juga menganalisis dan menjabarkan tentang skema atau alur yang metode promethee yang bisa digunakan oleh mahasiswa serta kriteria dasar seperti akademik, keaktifan, sikap dan kepercayaan diri yang dimiliki. Kriteria dasar ini bisa menjadi salah satu referensi pedoman yang digunakan dalam tahap penyeleksian dan pengambilan keputusan. Kata kunci: himpunan mahasiswa; promethee; sistem pengambilan keputusan,